Pengaruh Online Shopping terhadap Peningkatan Kinerja Green Marketing pada Kaum Milenial di Beberapa Kota Besar - Abdul Aziz; Hafiz Rahman; Rida Rahim; Hendra Lukito; Syafrizal Syafrizal (Politeknik Ganesha Medan, 2023)
This study aims to determine how much influence online shopping has on improving green marketing performance. The object of research is millennials in several big cities who are considered worthy of research and have a major influence on the development of online shopping and environmental preservation. The data collection process was carried out by filling out a questionnaire which was distributed via WhatsApp. The results of the study show that there is no significant effect of online shopping for the millennial generation on increasing green marketing performance. The moderating variable which contains knowledge about the importance of preserving the environment shows a significant influence on green marketing performance, but is unable to change purchasing decisions for millennials to buy environmentally friendly products. From an analysis of the buying behavior of the millennial generation in online shopping, it was found that the millennial generation understands the importance of protecting the environment. There are several reasons why the millennial generation is not interested in shopping for environmentally friendly products or